A Comparison of Two Pain Scales in the Assessment of Dental Pain in East Delhi Children - Khatri, Amit (International Scholarly Research Network, 2012)
Pain is the most common symptom of oral diseases. Pain perception in children is highly variable and unreliable due to poor communication. Therefore we designed a study to compare pain measurement techniques, that is, visual analogue scale (VAS) and Wong-Baker faces pain rating scale (WBFPS) among Delhi children aged 3 to 14 years undergoing dental extraction. Method. A cross-sectional study was conducted on 180 patients aged 3 to 14 years who had undergone dental extraction. Children were assessed for their pain sensitivity using visual analogue scale (VAS) and Wong-Baker faces pain rating scale (WBFPS ). Result and Conclusion. Pain threshold tends to decline, and the self-management of pain becomes more effective with increasing age. Genderwise result shows that communication ability of boys and girls is similar in all age groups.